Complete mitochondrial DNA genome of Polytremis nascens (Lepidoptera: Hesperiidae). (2nd September 2016) - Jiang, Weibin; Zhu, Jianqing; Yang, Qichang; Zhao, Huidong; Chen, Minghan; He, Haiyan; Yu, Weidong
Abstract: In this study, the complete mitochondrial DNA (mtDNA) sequence of Polytremis nascens (Lepidoptera: Hesperiidae) was determined. The 15, 392 bp mitogenome with GenBank accession number KM981865 contained 13 protein genes, 22 tRNAs, 2 rRNAs, and a non-coding control region (D-loop). All the 37 typical animal mitochondrial genes were found. The overall base composition was 39.7% A, 40.7% T, 7.7% G and 11.9% C, with a high A + T content (80.4%). This complete mitogenome of P. nascens provides a basic data for studies on species identification, molecular systematics and conservation genetics.